The two “rules of speciation” in species with young sex chromosomes - Filatov, D (Wiley, 2018)
The two “rules of speciation,” Haldane's rule (HR) and the large‐X effect (LXE), are thought to be caused by recessive species incompatibilities exposed in the phenotype due to the hemizygosity of X‐linked genes in the heterogametic sex. Thus, the reports of HR and the LXE in species with recently evolved non‐ or partially degenerate Y‐chromosomes, such as Silene latifolia and its relatives, were surprising. Here, I argue that rapid species‐specific degeneration of Y‐linked genes and associated adjustment of expression of X‐linked gametologs (dosage compensation) may lead to rapid evolution of sex‐linked species incompatibilities. This process is likely to be too slow in species with old degenerate Y‐chromosomes (e.g., in mammals), but Y‐degeneration in species with young gene‐rich sex chromosomes may be fast enough to play a significant role in speciation. To illustrate this point, I report the analysis of Y‐degeneration and the associated evolution of gene expression on the X‐chromosome of S. latifolia and Silene dioica, a close relative that shares the same recently evolved sex chromosomes. Despite the recent (≤1MY) divergence of the two species, ~7% of Y‐linked genes have undergone degeneration in one but not the other species. This species‐specific degeneration appears to drive faster expression divergence of X‐linked genes, which may account for HR and the LXE reported for these species. Furthermore, I suggest that “exposure” of autosomal or sex‐linked recessive species incompatibilities in the haploid plant gametophyte may mimic the presence of HR in plants. Both haploid expression and species‐specific Y‐degeneration need to receive more attention if we are to understand the role of these processes in speciation.